THU0546 HEALTHCARE COSTS OF NOT ACHIEVING REMISSION IN PATIENTS WITH RHEUMATOID ARTHRITIS. (2nd June 2020) - Bergman, M.; Zhou, L.; Patel, P.; Sawant, R.; Clewell, J.; Tundia, N.
Abstract : Background: Guidelines recommend sustained remission as a treatment goal for patients with rheumatoid arthritis (RA). However, only one-third of patients are known to achieve this goal with current treatments. A few studies have evaluated the impact of remission in a real-world setting, but evidence is limited to the elderly population. Objectives: To understand the impact of remission on healthcare costs by comparing overall and RA-related direct healthcare costs and resource use in patients with RA who maintain vs those who do not maintain remission using a real-world database. Methods: Data for this retrospective cohort study were derived from Optum electronic health records linked to claims from commercial and Medicare Advantage health plans in the United States. Patients with ≥2 diagnoses for RA, ≥1 Disease Activity Score 28 (DAS28-CRP/ESR) or Routine Assessment of Patient Index Data 3 (RAPID3) measurement, and continuous medical and pharmacy coverage 6 months before and 1 year after the index date were included. Two cohorts were created: remission and non-remission. Remission was defined as DAS28 <2.6 or RAPID3 ≤3.0. In the remission cohort, the index date was defined as the first date remission was achieved. In the non-remission cohort, the index date was defined as the first date of DAS28 or RAPID3 measurement. Outcomes were all-cause and RA-related total, medical, and prescription costs; healthcare resource use (number of inpatient, emergency department [ED], outpatient, and other visits); and number of prescriptions within 1 year of index date. A weighted generalized linear model and binomial regression were used to estimate adjusted annual direct costs and healthcare resource use, respectively. Confounding between cohorts due to age, sex, race and comorbidities using the Elixhauser index was controlled for in the models. Results: A total of 335 patients with RA (remission cohort: 125; non-remission cohort: 210) met the study inclusion criteria. Annual all-cause total direct costs in the remission cohort were significantly less than in the non-remission cohort ($30, 427 vs $38, 645, respectively; cost ratio (CR)=0.79; 95% CI: 0.63, 0.99). All-cause medical costs were significantly lower in the remission cohort than in the non-remission cohort (Figure 1 ); furthermore, among all-cause medical costs, outpatient visit costs were significantly lower in the remission than in the non-remission cohort. All-cause resource use (mean number of visits) was less in the remission vs non-remission cohort: inpatient (0.23 vs 0.63; visit ratio (VR)=0.36; 95% CI: 0.19, 0.70), ED (0.36 vs 0.77; VR=0.47; 95% CI: 0.30, 0.74), and outpatient visits (20.7 vs 28.5; VR=0.73; 95% CI: 0.62, 0.86). Annual RA-related total direct costs were similar in both cohorts (Figure 2 ); however, RA-related medical costs were numerically lower in the remission vs non-remission cohort ($8, 594 vs $10, 002, respectively; CR=0.86; 95% CI: 0.59, 1.25). RA-related resource use (mean number of visits) was less in the remission vs non-remission cohort: inpatient (0.15 vs 0.22; VR=0.67; 95% CI: 0.35, 1.30), ED (0.04 vs 0.13; VR=0.31; 95% CI: 0.10, 0.95), and outpatient visits (5.4 vs 7.4; VR=0.72; 95% CI: 0.58, 0.91). Conclusion: Significant economic burden was associated with patients who did not maintain remission compared with those who maintained remission. Although outpatient visits were the driver of medical costs in both groups studied in this analysis, the contribution of outpatient visits was greater among those who did not maintain remission. Acknowledgments: Financial support for the study was provided by AbbVie. AbbVie participated in the interpretation of data, review, and approval of the abstract. All authors contributed to the development of the publication and maintained control over the final content. Medical writing services were provided by Joann Hettasch of JK Associates Inc., a member of the Fishawack Group of Companies, and funded by AbbVie. Disclosure of Interests: Martin Bergman Shareholder of: Johnson & Johnson – stockholder, Consultant of: AbbVie, BMS, Celgene Corporation, Genentech, Janssen, Merck, Novartis, Pfizer, Sanofi – consultant, Speakers bureau: AbbVie, Celgene Corporation, Novartis, Pfizer, Sanofi – speakers bureau, Lili Zhou Shareholder of: AbbVie, Employee of: AbbVie, Pankaj Patel Shareholder of: AbbVie, Employee of: AbbVie, Ruta Sawant Shareholder of: AbbVie, Employee of: AbbVie, Jerry Clewell Shareholder of: AbbVie, Employee of: AbbVie, Namita Tundia Shareholder of: AbbVie, Employee of: AbbVie